Improved PKS Gene Expression With Strong Endogenous Promoter Resulted in Geldanamycin Yield Increase. Issue 11 (4th September 2017) - Wang, Xinran; Ning, Xinjuan; Zhao, Qinqin; Kang, Qianjin; Bai, Linquan
Abstract : The type I polyketide geldanamycin is a potent anti‐tumor reagent. Its biosynthesis includes three steps: the biosynthesis of precursors, such as 3‐amino‐5‐hydroxybenzoic acid (AHBA), the polyketide synthase (PKS) chain extension, and the post‐PKS modifications. According to the genomic and transcriptomic analysis, the PKS chain extension was deduced to be the rate‐limiting step for geldanamycin production in Streptomyces hygroscopicus XM201. In order to improve the expression of PKS genes, a strong endogenous promoter 5063p was obtained based on the transcriptomic analysis and XylE enzymatic assay. By replacing the native PKS promoter gdmA1p with 5063p, the expression of the PKS genes during geldanamycin fermentation was increased by 4–141‐folds, and the geldanamycin yield was increased by 39%. Interestingly, AHBA feeding experiment showed that the supply of AHBA in turn become a new rate‐limiting factor for geldanamycin production. Further combined overexpression of the 6‐gene AHBA biosynthetic cassette and PKS genes increased the yield of geldanamycin by 88%, from 773 mg L −1 of the wild‐type to 1450 mg L −1 in the derived strain. Our results suggested that improved expression of all PKS genes in a particular biosynthetic gene cluster is important for the yield increase of the corresponding polyketide natural product. Abstract : Geldanamycin is a strong antitumor reagent. In this study, the polyketide synthase (PKS) chain extension step in geldanamycin biosynthesis is speculated to be the rate‐limiting step and is relieved by in situ overexpressing the 40 kb PKS genes, with a strong screened endogenous promoter. This work suggests that improved expression of all PKS genes in a particular biosynthetic gene cluster is important for the yield increase of the corresponding polyketide natural product.